2018
DOI: 10.1253/circj.cj-17-0463
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implication of Transaortic Mitral Pannus Removal During Repeat Cardiac Surgery for Patients With Mechanical Mitral Valve

Abstract: Background: This study aimed to evaluate the safety and feasibility of transaortic mitral pannus removal (TMPR). Methods and Results:Between 2004 and 2016, 34 patients (median age, 57 years; 30 women) with rheumatic disease underwent pannus removal on the ventricular side of a mechanical mitral valve through the aortic valve during reoperation. The median time interval from the previous surgery was 14 years. TMPR was performed after removal of the mechanical aortic valve (n=21) or diseased native aortic valve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Recently, we reported our experience with transaortic mitral pannus removal during repeat cardiac surgery. 25 Subaortic pannus removal without repeat AVR is not recommended, because of incomplete hemodynamic improvement and the possibility of early recurrent subaortic stenosis. 7 The 10-year overall survival was 88%; however, the event-free survival at 10 years was only 51% because of recurrent prosthetic AS, paravalvular leakage of the mitral valve, prosthetic endocarditis, and TR progression after tricuspid valve repair.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported our experience with transaortic mitral pannus removal during repeat cardiac surgery. 25 Subaortic pannus removal without repeat AVR is not recommended, because of incomplete hemodynamic improvement and the possibility of early recurrent subaortic stenosis. 7 The 10-year overall survival was 88%; however, the event-free survival at 10 years was only 51% because of recurrent prosthetic AS, paravalvular leakage of the mitral valve, prosthetic endocarditis, and TR progression after tricuspid valve repair.…”
Section: Discussionmentioning
confidence: 99%
“…Their MVPG was 5 ± 1 mmHg, compared to 11 ± 7 mmHg ( p = 0.001). Park et al ( 16 ) found that patients with MVPG <5 mmHg could not benefit from the pannus clearance. Our findings were in line with their report.…”
Section: Discussionmentioning
confidence: 99%
“…Pannus formation was reported to occur more frequently in the aortic position and in female patients [ 18 , 19 ]. The incidence of pannus formation after mechanical MVR was reportedly below 1% [ 16 ], which is consistent with the present study (0%).…”
Section: Discussionmentioning
confidence: 99%